1987
DOI: 10.1016/0014-5793(87)80303-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear protein(s) binding to the conserved DNA hexameric sequence postulated to regulate transcription of wheat histone genes

Abstract: Nuclear protein(s) that specifically bind(s) to the upstream hexamer motif, ACGTCA, of wheat histone H3 and H4 genes has (have) been identified. Sequences homologous to this hexamer are found to be conserved in the upstream region of not only wheat histone genes but also other plant and animal histone genes. This suggests a possible role(s) for the hexamer and the nuclear protein(s) in the transcriptional regulation of the wheat histone genes. This hexamer is homologous to the upstream core sequence, TGACGTCA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…In addition to these motifs, there is also a pentanucleotide (TGACG) repeat located between -82 to -78 and -70 to -66 ( Figure 3). This pentanucleotide is highly homologous to the hexamer motif identified upstream of histone genes by Iwabuchi and co-workers (Mikami et al, 1987). The relative importance of these sequence motifs to the 35S activity is being evaluated.…”
Section: The -90 To -46 Region Plays An Accessory Role In Transcriptionmentioning
confidence: 89%
“…In addition to these motifs, there is also a pentanucleotide (TGACG) repeat located between -82 to -78 and -70 to -66 ( Figure 3). This pentanucleotide is highly homologous to the hexamer motif identified upstream of histone genes by Iwabuchi and co-workers (Mikami et al, 1987). The relative importance of these sequence motifs to the 35S activity is being evaluated.…”
Section: The -90 To -46 Region Plays An Accessory Role In Transcriptionmentioning
confidence: 89%
“…The basic region is implicated in DNA binding and the leucine zipper mediates homo-and heterodimerization. Several plant bZIP proteins have been shown to bind the ACGT cis-acting element identified in the promoters of bacterial, viral, and plant genes (Mikami et al 1987;Giuliano et al 1988;Bouchez et al 1989;Lam et al 1989;Schindler et al 1992aSchindler et al , 1992b. Based on their DNA-binding specificity and heterodimerization characteristics, these plant bZIP proteins can be classified into at least two classes: the G box (CCACGTGG)-binding factor (GBF) family and the TGACGT/C-binding proteins (Schindler et al 1992a;Foster et al 1994).…”
Section: Pan Encodes a Bzip Proteinmentioning
confidence: 99%
“…The as-1 element is able to confer expression primarily in root tissues, but also interacts synergistically with other cis-elements (Lam et al, 1989) and has been shown to bind AS1 tobacco nuclear factor (Fromm et al, 1989). This region also contains a sequence, ACGTCA, with homology to the hexamer motif of plant histone promoters (Mikami et al, 1987). The presence of this motif in the genomes of several other ssDNA plant viruses has been suggested to reflect an evolutionary conservation of transcription control mechanisms within this group (Morozov et al, 1994).…”
Section: Discussionmentioning
confidence: 99%